Sistema de comunicação e comando remoto de inversores utilizando o barramento de alimentação em corrente contínua - Gideon Igor Carvalho Lobato (2014)
This work aims to evaluate the use of long dc bus as the transmission medium for data exchange and command of frequency converters. This technology is particularly interesting in applications where the inverter / motor is in inaccessible places, as in the case of subsea oil extraction, where the power generation is located on the platforms while the motor is installed on the seabed. With increasing of cable length, issues relating to noise and attenuation imposed by the bus become particularly interesting. This work presents simulation and experimental results, which demonstrate the efficiency and applicability of this technology for dc bus with cable length a few hundred.